Early but not late conformational changes of tau in association with ubiquitination of neurofibrillary pathology in Alzheimer's disease brains - Ibarra-Bracamontes, Vanessa J; Escobar-Herrera, Jaime; Kristofikova, Zdena; Rípova, Daniela; Florán-Garduño, Benjamín; Garcia-Sierra, Francisco (Brain research, 2020)
In Alzheimer's disease, tau protein undergoes post-translational modifications including hyperphosphorylation and truncation, which promotes two major conformational changes associated with progressive N-terminal folding. Along with the development of the disease, tau ubiquitination was previously shown to emerge in the early and intermediate stages of the disease, which is closely associated with early tau truncation at aspartic acid 421, but not with a subsequently truncated tau molecule at glutamic acid 391. In the same group of cases, using multiple immunolabeling and confocal microscopy, a possible relationship between the ubiquitin-targeting of tau and the progression of conformational changes adopted by the N-terminus of this molecule was further studied. A comparable number of neurofibrillary tangles was found displaying ubiquitin, an early conformation recognized by the Alz-50 antibody, and a phosphorylation. However, a more reduced number of neurofibrillary tangles were immunoreactive to Tau-66 antibody, a late tau conformational change marker. When double-labeling profiles of neurofibrillary tangles were assessed, ubiquitination was clearly demonstrated in tau molecules undergoing early N-terminal folding, but was barely observed in late conformational changes of the N-terminus adopted by tau. The same pattern of colocalization was visualized in neuritic pathology. Overall, these results indicate that a more intact conformation of the N-terminus of tau may facilitate tau ubiquitination, but this modification may not occur in a late truncated and more compressed folding of the N-terminus of the tau molecule.
Keywords: mozek; Humans; ubikvitinace; lidé středního věku; Female; Aged; Protein Conformation; tau Proteins; senioři; lidé; Alzheimer Disease; Alzheimerova nemoc; Neurofibrillary Tangles; proteiny tau; ženské pohlaví; Male; Ubiquitination; Middle Aged; Brain; Aged, 80 and over; senioři nad 80 let; mužské pohlaví; neurofibrilární klubka; konformace proteinů